EFEKTIVITAS PEMBELAJARAN INOVATIF MENGGUNAKAN POWTOON TERHADAP HASIL BELAJAR SISWA PADA MATERI TEKANAN ZAT DI SMP NEGERI 2 DUMOGA - Nurul Pratiwi; Armstrong Sompotan; Jimmy Lolowang (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2023)
This study aims to determine the effectiveness of the use of powtoon learning media on science learning outcomes, especially the substance pressure material for class VIII A students at SMP Negeri 2 Dumoga. The type of research used in this research is experimental research with a pre-experimental research design in the form of a one group pretest posttest design, with a quantitative research approach. In this study, the sample was taken using a total sampling technique with class VIII A as the research sample. The results of the study, it showed that: (1) the average score of student learning outcomes after the application of powtoon learning media was 86.4286 while before being given treatment it was 64.5714. (2) there is an increase in student learning outcomes after applying powtoon learning media by obtaining an average gain value of 0.7342 which is in the high criteria. As for the n-gain percent obtained 73.4177 which is in the criteria of being quite effective. (3) the result of the t-test with the paired sample t-test is 0.01, which means that is accepted. From the results of this study it can be concluded that the use of powtoon learning media is effective for science learning outcomes on substance pressure material for class VIII students of SMP Negeri 2 Dumoga.